Assessment of Financial Sustainability of Local Budgets in the Budget Management System Using Kohonen Maps - Lysiak, Liubov; Лисяк, Любов Валентинівна; Kachula, Svitlana; Качула, Світлана Валентинівна; Kushnir, Anna; Кушнір, Анна Ігорівна; Datsenko, Viktоriia; Даценко, Вікторія Володимирівна; Tereshchenko, Tetiana; Терещенко, Тетяна Євгеніївна (Horizon Research, 2021)
Systematic assessment of the financial stability of local budgets is important for timely detection of budget imbalances and identification of their causes, thus helping to make informed management decisions of current and strategic nature on the development of territories, quality local public services and improving welfare. The article proposes the use of Kohonen maps to determine the financial stability of local budgets. The main advantages of the practical use of Kohonen maps for this purpose compared to such common assessment methods as integrated and matrix are the simplification of the process of assessing the financial stability of local budgets and at the same time visualization of the results for public presentation. On Ukraine`s example local budgets were grouped according to the parameters of their financial stability with the construction of Kohonen maps based on the SOM-Ward algorithm. It allowed determining the financial condition of local budgets of Ukraine during 2017-2020 and accordingly the type of their financial stability. Taking into account changes in the financial stability of local budgets over time is important when adjusting fiscal policy. The idea is that simplifying the process of assessing the financial stability of local budgets is an important condition for its active practical application and at the same time will allow visualizing information for the public about local budgets which will promote transparency in budget management, and increase trust in the formation of priorities of fiscal policy at the local level. Системна оцінка фінансової стійкості місцевих бюджетів має важливе значення для своєчасного виявлення бюджетних дисбалансів та виявлення їх причин, що сприяє прийняттю обґрунтованих управлінських рішень поточного та стратегічного характеру щодо розвитку територій, якісних місцевих державних послуг та підвищення добробуту населення. У статті пропонується використовувати карти Кохонена для визначення фінансової стійкості місцевих бюджетів. Основними перевагами практичного використання для цієї мети карт Кохонена порівняно з такими поширеними методами оцінки, як інтегральний та матричний, є спрощення процесу оцінки фінансової стійкості місцевих бюджетів і водночас візуалізація результатів для публічного представлення. На прикладі України місцеві бюджети були згруповані за параметрами їх фінансової стійкості з побудовою карт Кохонена на основі алгоритму SOM-Ward. Це дозволило визначити фінансовий стан місцевих бюджетів України протягом 2017-2020 років і відповідно вид їх фінансової стійкості. Урахування змін фінансової стійкості місцевих бюджетів у часі є важливим при коригуванні фіскальної політики. Ідея полягає в тому, що спрощення процесу оцінки фінансової стабільності місцевих бюджетів є важливою умовою його активного практичного застосування і водночас дозволить наочно надати громадськість інформацію про місцеві бюджети, що сприятиме прозорості в управлінні бюджетом, підвищить довіру. у формуванні пріоритетів фіскальної політики на місцевому рівні.
Оцінка фінансової стійкості місцевих бюджетів у системі управління бюджетом за допомогою карт Кохонена
Keywords: Ukraine; Україна; Local Budget; місцевий бюджет; Budget System; бюджетна система; Financial Stability; фінансова стабільність; Budget Management; управління бюджетом; Kohonen's Self-Organization Map; карти Кохонена